PEMBELAJARAN IPS DI SMP NEGERI 3 CANDI LARAS UTARA DI KABUPATEN TAPIN - Hariyadi Hariyadi (Universitas Lambung Mangkurat, 2016)
This research aims to find out how the competency of teachers involved in the teaching and learning process of Social Science at SMP Negeri 3 Candi Laras Utara.This research appliedqualitative method. The researcher tried to do exploration in plan of getting data naturally in field through observation and communication with all existing data sources. The process of data collectionin this researchwas done through few steps namely observation, documentation and triangulation. The researcher used credibility test of the data for validity checking in the effort of obtaining data which is objective, reliable, valid and can be accounted for.Based on the result of the research, it is understood that: (1) the teachers of Social Science have all professional, personality, pedagogical and social competence; (2) the process of Social Science teaching and learning has fulfilled the minimum level of process standard including the preparation, implementation, and evaluation although the methods of teaching are not maximally yet explored; (3) the teachers used textbooks and printed material as learning resources which are available in the library; (4) the facility and infrasructure which are available in the classroom and the library are still limited; (5) the problem faced by the Social Science teacher is the insufficient facility and infrastructure to support Social Science teaching and learning, either it is related to the teaching and learning media andsources of study, or the educational background of the teachers when teaching integrated Social Science.Key Words: Teaching and learning of social science, teacher competence, learning resources, infrastructure, evaluation Penelitian ini bertujuan untuk mengetahui kompetensi guru yang terlibat dalam proses pembelajaran IPS di SMP Negeri 3 Candi Laras Utara. Penelitian ini menggunakan metode kualitatif, peneliti berusaha untuk melakukan eksplorasi dalam rangka mendapatkan data secara alamiah di lapangan melalui observasi dan komunikasi dengan berbagai sumber yang ada. Proses pengumpulan data yang dilakukan pada penelitian dengan beberapa tahap yaitu observasi, wawancara, dokumentasi, dan trianggulasi. Peneliti menggunakan uji kredibilitas data untuk pengecekan keabsahan data dalam penelitian dilakukan untuk memperoleh data yang objektif, andal, sahih dan dapat dipertanggungjawabkan.Berdasarkan hasil penelitian diketahui (1) kompetensi guru IPS memeliki kemampuan profesional, kepribadian, pedagogik dan sosial, (2) proses pembelajaran IPS telah memenuhi standar proses minimal meliputi persiapan, pelaksanaan, dan evaluasi, tidak secara maksimal dalam melaksanakan metode pembelajaran, (3) guru menggunakan sumber buku teks pelajaran dan media cetak yang tersedia di perpustakaan (4) sarana dan prasarana yang tersedia ruang kelas dan perpustakaan yang menyediakan media dan buku pelajaran yang masih terbatas, (5) Permasalahan yang dihadapi oleh guru dalam pembelajaran IPS adalah terbatasnya sarana prasarana yang menunjang pembelajaran IPS, baik itu berhubungan dengan media pembelajaran maupun sumber belajarnya, dan latar belakang pendidikan guru pada saat mengajar pembelajaran IPS terpadu.Kata Kunci: Pembelajaran IPS, kompetensi guru, sumber belajar, sarana prasarana, evaluasi